Foreign direct investment as a pull factor of the economic growth in Ukraine in the period 2003-2016 - Marta Voloshyn (International Entrepreneurship Review, 2018)
Objective: The aim of this paper is to present the results of investigation of the interlink between FDI and the economic growth in Ukraine in the period 2003-2016.